In love and struggle : the revolutionary lives of James and Grace Lee Boggs - Ward, Stephen M., 1970- (Justice, power, and politics., 2016)
"James and Grace Lee Boggs were two largely unsung but critically important figures in the black freedom struggle. James Boggs was the son of an Alabama sharecropper who came to Detroit during the Great Migration, becoming an automobile worker and a union leader. Grace Lee was a Chinese American scholar who studied Hegel, worked with Caribbean political theorist C.L.R. James, and moved to Detroit to work toward a new American revolution. As husband and wife, the couple was influential in the early stages of what would become the Black Power movement, laying the intellectual foundation for labor and urban struggles during one of the most active social movement periods in modern U.S. history. Stephen Ward details both the personal and the political dimensions of the Boggses' lives, highlighting the vital contributions these two figures made to black activist thinking"--